Peptic ulcer disease among dyspeptic patients at endoscopy unit, University of Gondar hospital, Northwest Ethiopia - Assefa, Belete; Tadesse, Abilo; Abay, Zenahebezu; Abebe, Alula; Tesfaye, Tsebaot; Tadesse, Melaku; Molla, Ayenew (BMC gastroenterology, 2022)
Background Dyspepsia is a common complaint in upper gastrointestinal disorders. It is described as predominant epigastric pain lasting for at least one month. Globally, peptic ulcer disease occurs in 3.5–32% of patients with dyspepsia. Helicobacter pylori ( H. pylori ) infection and non-steroidal anti-inflammatory drugs/aspirin use are the widely known risk factors for peptic ulcer disease. There was no recent document on H. pylori infection rate among patients with peptic ulcer disease in Ethiopia. This study aimed to determine magnitude and associated factors of peptic ulcer disease among dyspeptic patients in Northwest Ethiopia. Methods An institutional-based cross sectional study was conducted at the University of Gondar hospital, Northwest Ethiopia. A convenience sampling method was used to recruit 218 study subjects. A pre-designed semi-structured questionnaire was used to extract clinical information. Olympus flexible fiber-optic endoscope (Olympus, GIF-E 600, Olympus Corp., Hamburg, Germany) was used to confirm the presence of peptic ulcer disease. Diagnosis of active H. pylori infection was made using the fecal H. pylori Antigen 25 T Card Test (Anamol Lab., Pvt. Ltd., Palghar, India). The Data were entered into EPI Info version 4.6.0.2, and then exported to SPSS version 20 for analysis. Explanatory variables associated with peptic ulcer disease were analyzed by applying logistic regression model. P value < 0.05 was used to declare significant association. Result A total of 218 dyspeptic patients who underwent upper gastrointestinal endoscopic evaluations were included in the study. The mean (+ SD) age of patients was 42 ± 16.4 years. Forty nine percent (95% CI 42.4–56.2) of dyspeptic patients had active H. pylori infection. Peptic ulcer disease was diagnosed in 35% (95% CI 31.4–39.2) of patients with dyspepsia. H. pylori infection (AOR = 6.298, 95% CI 2.965–13.378, P value <  0.001) and NSAIDs/ASA use (AOR = 6.252, 95% CI 2.925–13.362, P value <  0.001) were identified as risk factors for peptic ulcer disease. Conclusion Medical treatment of peptic ulcer disease should target treatment of H. pylori infection and cautious use of non-steroidal anti-inflammatory drugs/aspirin.